UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETIL ASETAT KULIT AKAR SENGGUGU (Clerodendrum serratum) ASAL IMOGIRI, YOGYAKARTA - Nasrudin Nasrudin; Mustofa Mustofa; Ratna Asmah (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2017)
ABSTRACT Senggugu (Clerodendrum serratum) is one of the potential plants as the source of natural antioxidant. Traditionally, some Asian countries, as well as Indonesia, has been applied this plant for treatment in various diseases. The leaf and stems of Clerodendrum pholimidis and Clerodendrum viscosum that are the same genus with senggugu indicated that they are potential as an antioxidant. The Senggugu plants growing in India, China and Malaysia have been reported that the extracts of the plant are also active as an antioxidant. The objective of this work is to study antioxidant activity of ethyl acetate extracts of the senggugu root-stem collected from Imogiri, Yogyakarta. The extract was obtained through sequential maceration technique using n-hexane, ethyl acetate, and methanol solvents. The antioxidant activity of the extract was then examined by DPPH (2,2-dipphenyl-1-pycryl hydrazyl) and rutin as the standard antioxidant. The results showed that the ethyl acetate extracts of root-stem of the senggugu have antioxidant activity property with IC50 of 30.968±0.686 μg/mL and IC50 of 1.741±0.091 μg/mL for rutin as the standard antioxidant. Key words: Root-stem, Clerodendrum serratum, antioxidant